The Paradigm Shift - Rhetoric or Reality? - Loven, Anders [Verfasser] (My University, 2003)
"This article discusses changes in working life and other aspects of life and their significance for counselling andguidance. It focuses on a shift in research, international debate and goal documents ratherthan in counselling practice. The paradigmshift refers to the change from a modern to amore post-modern view, which means that counselling should be oriented more towards the whole person and his or her life projects. The aim in this perspective is to make clients more proactive in constructing their own lives. Someclients, however, are still stuck in a passive and helpless role. This is a great challenge for counsellors who are striving to develop more holistic working methods. The transition from a modern to a more post-modern society requires a counsellor with a wide arsenal of interventions and many working tools, i.e. amulti- instrumentalist. The conclusion is that counsellors have to be more aware of the different situations, expectations and forms of behaviour faced by clients. Counsellors have to develop new methods centred round the clients'self-activity. " (author's abstract, IAB- Doku) ((en))
Keywords: L 5 Beratung & Orientierung; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 1.2 Arbeitsmarkt; G 2.3.5 Wirtschaftsstrukturwandel; G 2.4.2 Lebenskonzepte, -stile, Werte; T 4.2 Psychologie; I 2.2.1 Westeuropa; Berufsberatung; Berufswahlvorbereitung; Arbeitswelt; Strukturwandel; Persönlichkeitsentwicklung; Lebensplanung; Schweden